2015
DOI: 10.1002/pssa.201431743
|View full text |Cite
|
Sign up to set email alerts
|

Physics‐based modeling and experimental implications of trap‐assisted tunneling in InGaN/GaN light‐emitting diodes

Abstract: In a combined experimental and numerical investigation, we present the effects of trap-assisted tunneling on the sub-threshold forward bias characteristics of a blue InGaN/GaN single-quantum-well LED test structure grown on a SiC substrate. The different role of donor- and acceptor-like traps has been studied, for the information it can provide on the role played by point defects. Using the energy Et and trap density Nt as the only tunneling-related fitting parameters, the behavior of the measured I(V) curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…In the range of the forward bias at which tunneling occurred, SRH nonradiative recombination was the dominant process in the LED operation. The result was consistent with the reports on trap-assisted tunneling, which employed SRH recombination in the models [17][18][19]. As the DSDRs have a high density of nonradiative recombination defects, which affect the chip operation, the adoption of the PL imaging technique to detect DSDRs can provide an effective inspection and a quick evaluation of LED epi-wafers, allowing the estimation of the properties of the LED chips fabricated from the epi-wafers.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the range of the forward bias at which tunneling occurred, SRH nonradiative recombination was the dominant process in the LED operation. The result was consistent with the reports on trap-assisted tunneling, which employed SRH recombination in the models [17][18][19]. As the DSDRs have a high density of nonradiative recombination defects, which affect the chip operation, the adoption of the PL imaging technique to detect DSDRs can provide an effective inspection and a quick evaluation of LED epi-wafers, allowing the estimation of the properties of the LED chips fabricated from the epi-wafers.…”
Section: Discussionsupporting
confidence: 88%
“…Their result suggested that a high dislocation density could be the reason for the high ideality factors. Recently, forward leakage at low and intermediate bias region has been explained considering trap-assisted tunneling [13,[17][18][19]. The results in this work indicate that the DSDRs in LED-4 are regions of high density of dislocations and deep traps, which cause the forward leakage.…”
Section: I-v Characteristics Of Led Chips With Dsdrsmentioning
confidence: 75%
See 2 more Smart Citations
“…[10][11][12][13]), which cannot genuinely account for hot carriers and generally also produces larger turnon voltages for MQW LEDs than observed experimentally. [14] Many reasons have been suggested to explain this discrepancy, including charge transport through indium fluctuations, [15] V-shaped pits, [16] tunneling through traps [17] or hot carrier transport. [18] At present it is, however, unclear if the discrepancy is of a physical origin or if it arises simply because the very foundations of the widely adopted DD model make it incapable of predicting the most essential device-level characteristics of LEDs.…”
Section: Doi: 101002/aelm201600494mentioning
confidence: 99%